Tinjauan Ketepatan Koding Penyakit Gastroenteritis Pada Pasien BPJS Rawat Inap di UPTD RSUD Kota Salatiga - Elise Garmelia; Maulida Sholihah (Poltekkes Kemenkes Semarang, 2019)
One of the factors causing the inaccuracy of writing diagnosis code is sometimes doctors do not write the diagnosis in the complete form so that medical record errors occur in determining the diagnosis code. Based on preliminary studies that researchers have done in UPTD RSUD Salatiga, the researchers found the results of encoding gastroenteritis disease is inappropriate. Researchers took a random sample, from 8 medical records of patients with BPJS gastroenteritis inpatient there were 6 medical records showing the inaccuracy of encoding diagnosis with 75% percentage of incorrect code and there was different writing of gastroenteritis diagnosis on admission discharge form and discharge summary form.The purpose of this study to determine the accuracy of coding disease gastroenteritis. The type of the research is descriptive quantitative research using cross sectional approach. The population in this research is medical record of inpatients of BPJS gastroenteritis case in january 2017 until october 2017, with the sample of 82 medical record by using simple random sampling method.The results showed the percentage of appropriateness of writing diagnosis on the outline forms form outgoing and returning home is 93.9%, the percentage of accuracy of gastroenteritis disease code is 91.5% and the percentage of appropriateness of diagnosis with the result of laboratory examination is 89%. Factors affecting the inaccuracy of coding results are that medical personnel (physicians) write incomplete and incompatible patients' diagnostic diagnosis of the form sheet, the coder does not check the results of the laboratory to determine the correct code, the lack of update activity of the ICD-10 coding latest version.Of these factors can affect the quality of medical records with the results of coding, claims results and analysis of hospital reporting data.